DISCOURSE ANALYSIS: SOME CONCEPTUAL REMARKS ON PRAGMATICS AND RHETORIC - Abd. Ghofur (IAIN MADURA, 2011)
This paper focuses on discourse analysis, particularly persuasive discourse, using pragmatics and rhetoric in a combined way, called by Pragma-Rhetoric. It can be said that this is a cognitive approach to both pragmatics and rhetoric. Pragmatics is essentially Gricean, Rhetoric comes from a reading of Aristotle’s Rhetoric, extending his notion of discourse to meso- and micro-discourses. Two kinds of intentions have to be considered: first, communicative intention, and, then, persuasive intention. The fulfilment of those intentions is achieved by a successful persuasive-communicative action. The psychological, philosophical and logical aspects derived from the pragma-rhetorical perspective are crucial in view of its applications in several practical domains.